The Potential of Positive Affirmations to Addressing Body Image Concerns among Individuals with Diabetes Mellitus - Arianti, Diana; Susanti, Amelia; Gusdiansyah, Edo; Welly (RRZ Scientific Publishing, 2024)
Body image disturbances are a common psychological challenge among patients with Diabetes Mellitus (DM), influenced by the physical and emotional toll of the disease. Body dissatisfaction can negatively impact self-esteem, adherence to diabetes management, and overall quality of life. Positive affirmations, rooted in self-affirmation theory, have improved body image in various populations. However, there is limited research on the application of positive affirmations as an intervention for body image in DM patients. This study evaluated the effectiveness of a structured, positive affirmation intervention in improving body image among patients with Diabetes Mellitus using a quasi-experimental one-group pretest-posttest design. The study involved 40 adult DM patients participating in a 4-week positive affirmation program. Body image outcomes were measured pre-and post-intervention using the Multidimensional Body-Self Relations Questionnaire – Appearance Scale (MBSRQ-AS). The primary outcomes were changes in appearance evaluation, appearance orientation, body area satisfaction, and self-classified weight. Paired sample t-tests were used to analyze pre- and post-intervention differences, with effect sizes calculated using Cohen's d. Significant improvements were observed in appearance evaluation (p < 0.001, d = 0.91), body area satisfaction (p < 0.001, d = 0.80), and self-classified weight (p < 0.01, d = 0.76). Appearance orientation decreased significantly (p < 0.01, d = 0.66), indicating a reduced focus on external appearance. The intervention showed firm effect sizes across all body image dimensions. Positive affirmations effectively improved body image among DM patients, with significant improvements across multiple dimensions. This intervention offers a practical, low-cost strategy for addressing body image disturbances, potentially enhancing the psychological and physical wellbeing of DM patients. Future studies should explore long-term effects and compare the intervention with other psychosocial approaches in diverse populations.